2015
DOI: 10.1007/s00128-015-1475-y
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Bioaccumulation and Health Hazard Assessment for Three Fish Species from Nansi Lake, China

Abstract: Metal accumulation in fish is a global public health concern, because the consumption of contaminated fish accounts for the primary exposure of humans to toxic metals. In this study, the concentrations of arsenic (As), cadmium (Cd), lead (Pb), and mercury (Hg) in Crucian carp (Carassius auratus),Yellow catfish (Pelteobagrus fulvidraco), and Bighead carp (Hypophthalmichthys nobilis) from Nansi Lake of China were evaluated, and compared with the corresponding historical values in 2001 when the government started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
4
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 17 publications
4
17
4
5
Order By: Relevance
“…THQ values greater than 1 indicate that a potential health risk may occur. Our results demonstrated that the THQ of individual metals did not pose a potential risk, but the total THQ exceeded the classification of no risk level (total THQ[1), as recommended by the USEPA (2000), suggesting direct health effects may be significant for the general population and especially for local inhabitants (Huang et al 2008;Krishna et al 2014;Li et al 2015). Thus, constant monitoring of both essential and non-essential metals remains very important to evaluate the risk for people consuming contaminated fish from the study area-and what can be done to lower this risk.…”
Section: Discussionmentioning
confidence: 49%
“…THQ values greater than 1 indicate that a potential health risk may occur. Our results demonstrated that the THQ of individual metals did not pose a potential risk, but the total THQ exceeded the classification of no risk level (total THQ[1), as recommended by the USEPA (2000), suggesting direct health effects may be significant for the general population and especially for local inhabitants (Huang et al 2008;Krishna et al 2014;Li et al 2015). Thus, constant monitoring of both essential and non-essential metals remains very important to evaluate the risk for people consuming contaminated fish from the study area-and what can be done to lower this risk.…”
Section: Discussionmentioning
confidence: 49%
“…If the THQ is >1, there is a risk to the health of the exposed population from consuming the product; if the THQ value is <1, there is no risk. In the current study, exposure to many pollutants (metals) was assessed; therefore, the total THQ or hazard risk (HI) was also calculated as the arithmetic sum of the individual metal THQ values, following the method of [26,27,31]. [Equation 2]:…”
Section: Target Hazard Quotientmentioning
confidence: 99%
“…Thus, accumulation occurs in the tissues of fish and can be transferred to higher trophic levels via food chain. Therefore, it is important to evaluate the concentration of toxic elements in fish, because it is representing a potential health risks to the fish organisms and to the higher trophic level organism like humans that potentially consume them (Li et al 2015;Vu et al 2017). Actually, numerous studies have been carried out on trace metals contamination of different species of edible fish (Prudente et al 1997;Kucuksezgin et al 2001;Lewis et al 2002;El Morhit et al 2009;Chahid et al 2014;Afandi et al 2015;Diop et al 2016).…”
Section: Introductionmentioning
confidence: 99%